Strong-texture bismuth-antimony flexible thermoelectric thin film and preparation method and application thereof
Through the melt-high pressure jet rotary quenching process and element doping technology, Bi1-xSbx thermoelectric film with high performance and flexibility characteristics was prepared, which solved the problem of insufficient optimal orientation of film (00l) in the prior art, and achieved an efficient and low-cost preparation process.
Patent Information
- Application Number
- CN202411852462.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-11
AI Technical Summary
It is difficult to efficiently prepare a micron-scale thickness Bi1-xSbx thermoelectric film with high performance and flexibility characteristics, and the (00l) preferential orientation of the film is insufficient.
The melt-high pressure jet rotary quenching process is adopted to reduce the formation energy of the Bi(012) surface through element doping, and the film is solidified in a direction along the (00l) direction, and a strong textured bismuth antimony flexible thermoelectric film is prepared.
It significantly improves the thermoelectric performance and flexibility characteristics of the film, realizes the (00l) optimal orientation, simplifies the preparation process, reduces costs, and improves the production efficiency of the device.
Smart Images

Figure CN119604177A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of functional materials, and in particular relates to a strongly textured bismuth-antimony flexible thermoelectric film and a preparation method and application thereof. Background Art
[0002] Thermoelectric materials can achieve temperature difference power generation and solid-state refrigeration through the conversion between heat energy and electrical energy. It is a green and clean energy conversion technology. In recent years, the power generation and refrigeration technology based on flexible thermoelectric films has shown broad application prospects in the fields of self-powered wearable devices and chip heat dissipation. 1-x Sb x ) alloy is recognized as one of the best thermoelectric materials in the temperature range of 50~250K. 1-x Sb x Planar thermoelectric devices have important commercial value in realizing liquefied natural gas cold source power generation and semiconductor low-temperature heat dissipation and temperature control.
[0003] In order to produce high-performance Bi 1-x Sb x Planar thermoelectric devices usually require the use of micrometer-thick films as thermoelectric arms. 1-x Sb x The main methods for thermoelectric thin films include magnetron sputtering, thermal evaporation and electrochemical deposition. However, the use of magnetron sputtering and evaporation processes to prepare thermoelectric thick films is not only time-consuming, but also has high target material costs and low utilization rates. 1-x Sb x The magnetron sputtering rate of the film is about 10μm / h, so it may take more than 100h to prepare a micron-thick film. In addition, although the use of organic-inorganic composite materials can efficiently prepare thermoelectric thick films through methods such as screen printing, the introduction of polymers will significantly reduce the thermoelectric performance of the film. On the other hand, the study pointed out that the (00 l ) Preferred orientation helps to improve the thermoelectric performance, however, the micron-thick Bi 1-x Sb x Thermoelectric films generally show low (00 l ) orientation. For example, Bi prepared by electrochemical deposition 1-x Sb x Thermoelectric films are usually oriented in the (102) direction, while nano-Bi 1-x Sb x The organic-inorganic composite film prepared by particles has almost no orientation. Therefore, how to efficiently and controllably prepare Bi with micron-level thickness and high performance is a key issue. 1-x Sb x Thermoelectric thin films have become an urgent problem to be solved in the application of low-temperature planar thermoelectric devices. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention aims to provide a strongly textured bismuth antimony flexible thermoelectric film and its preparation method and application. 1-x Sb x Thermoelectric properties and preparation efficiency of the film. The prepared thermoelectric film exhibits a strong (00 l ) oriented texture and high density, and at the same time has excellent thermoelectric performance and flexibility. In addition, the film can be directly mounted on a substrate for the preparation of planar thermoelectric devices, thereby improving the production efficiency of the device. The film preparation method involved in the present invention is simple, efficient, low-cost, and has good reliability and repeatability, and is very suitable for commercial mass production.
[0005] The purpose of the present invention is achieved through the following technical solutions: A strongly textured bismuth antimony flexible thermoelectric film, whose chemical structure is Bi 1-x-y Sb x Zn y , x=0.005~0.05, y=0~0.02; the thickness of the thermoelectric film is 10~100μm, and the film is along (00 l ) The orientation factor of the crystal plane is 0.55~0.78, and the power factor is 26~43μW·cm at 300K -1 ·K -2 .
[0006] Preferably, x=0.01~0.04, y=0~0.005; more preferably, x=0.035, y=0.005.
[0007] The method for preparing the above-mentioned strongly textured bismuth antimony flexible thermoelectric film comprises the following steps: (1) According to the component ratio of the target chemical structure, Bi, Sb, and Zn are mixed and melted at 500-800°C. After the reaction is completed, the reaction ingot is obtained by quenching with salt water; (2) The reaction ingot in step (1) is placed in a quartz tube with a nozzle and placed in a melt spinning quenching device; under a protective gas, the reaction ingot is melted by induction heating, and then a protective gas with a pressure of 0.1-0.2 MPa is input to form a high-speed jet of the molten alloy, which is sprayed from the nozzle onto a copper roller with a rotating linear speed of 8-20 m / s to complete high-pressure spray spinning quenching, and finally a continuous film is obtained.
[0008] Preferably, in step (1), the purity of Bi, Sb and Zn single substances is greater than 99.9%.
[0009] Preferably, in step (1), the heating rate of the melt reaction is 5-8°C / min.
[0010] Preferably, in step (1), the melting reaction time is 2 to 4 hours.
[0011] Preferably, in step (1), the temperature of the melting reaction is 500-600°C.
[0012] Preferably, in step (2), the gas injection pressure is 0.12-0.16 MPa.
[0013] Preferably, in step (2), the copper roller rotates at a linear speed of 10-15 m / s.
[0014] Preferably, in step (2), the size of the nozzle is 0.5-1 mm.
[0015] Preferably, in step (2), the protective gas is an inert gas or nitrogen; more preferably, the inert gas is argon.
[0016] The application of the above-mentioned strongly textured bismuth antimony flexible thermoelectric film in the preparation of low-temperature planar thermoelectric devices.
[0017] Compared with the prior art, the beneficial effects of the present invention include: (1) The present invention reduces the formation energy of Bi (012) surface during the solidification growth of the film by element doping, and realizes the formation of Bi (012) surface along the film by using melt-high pressure spray spinning quenching process. l ) direction, and finally the film obtains (00 l ) preferred orientation. This method significantly improves the thermoelectric performance of the film and gives it good flexibility.
[0018] (2) The micron-thick flexible film prepared by the present invention is not constrained by the substrate. Compared with the film prepared by magnetron sputtering, its structure and performance are not dependent on the substrate. The film can be mounted on substrates of different materials and directly used to prepare planar thermoelectric devices, showing flexible and efficient use characteristics.
[0019] (3) The present invention adopts a high-pressure jet spin quenching process to prepare a micron-thick high-performance thin film. Compared with magnetron sputtering, electrochemical deposition and other methods, the preparation cycle is significantly shortened to 3-5 hours, greatly improving the efficiency of thin film preparation and reducing costs. The present invention has the characteristics of simple and efficient process, controllable film quality, good reliability and repeatability, and low energy consumption. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 These are actual photographs of the strongly textured bismuth antimony flexible thermoelectric film prepared in Example 1, actual photographs of the film assembled into a planar device, and SEM microstructure photographs, where a is a actual photograph of the film, b is a actual photograph of the assembled planar device, and c~d are SEM microstructure photographs of the film.
[0021] Figure 2 This is a comparison chart of the EDS energy spectrum results of the films prepared in Example 1 and Comparative Example 1.
[0022] Figure 3 1 is the XRD diagram of the bismuth antimony thin films obtained in Examples 1 to 3 and Comparative Example 1.
[0023] Figure 4 The graphs are of the conductivity, Seebeck coefficient and power factor of the bismuth antimony thin films obtained in Examples 1 to 3 and Comparative Example 1 as a function of temperature, wherein a corresponds to the conductivity, b corresponds to the Seebeck coefficient, and c corresponds to the power factor. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0025] Example 1 A method for preparing a strongly textured bismuth antimony flexible thermoelectric film, the steps are as follows: (1) Using high-purity elemental Bi and Sb as the initial raw materials, according to the chemical formula Bi 0.96 Sb 0.04 The raw materials are weighed and sealed in a quartz tube under a high vacuum environment. The quartz tube is then placed in a muffle furnace for melting reaction. The temperature is raised to 600°C at a heating rate of 5°C / min and kept at this temperature for 2h. The bismuth-antimony master alloy ingot is obtained by quenching with brine (saturated brine).
[0026] (2) Place the bismuth-antimony master alloy ingot in a melt spinning quenching device, and maintain the vacuum degree of the chamber at 5×10 -3 Pa; then, under the protection of argon atmosphere, the master alloy ingot is melted by induction heating, and then high-pressure argon is input into the quartz tube to form a high-speed jet of the molten alloy, which is sprayed from the nozzle onto the rotating copper roller to complete the high-pressure spray spin quenching process, and finally a continuous film product is obtained. The specific process parameters are as follows: the spray pressure is 0.15 MPa, the copper roller linear speed is 10 m / s, the nozzle diameter is 0.5 mm, and the spray time is less than 10s; the spray time is related to the quality of the smelted metal, and the spray time is between 5 and 10s. In addition, the operation time of the initial vacuum and induction heating is 0.5h.
[0027] In the temperature range of 50-300K, the conductivity, Seebeck coefficient and power factor of the thermoelectric film prepared in Example 1 were tested. The test results are shown in Table 1.
[0028] Table 1 Performance results of the thermoelectric film described in Example 1
[0029] Note: In the table R / R 0 (Φ10mm, 100 times) refers to the ratio of the film resistance to the initial resistance after 100 bending cycles at a bending radius of 10 mm, the same below.
[0030] According to the data in Table 1, it can be seen that the film prepared in Example 1 has good thermoelectric properties. Further comparison with Table 4 shows that the performance of the film prepared in Example 1 is significantly better than that of Comparative Example 1, and its room temperature power factor is 38 μW·cm -1 ·K -2 Table 1 also shows that after 100 bending cycles at a bending radius of 10 mm, the ratio of the film resistance to the initial resistance remains essentially unchanged, demonstrating excellent flexibility.
[0031] Example 2 A method for preparing a strongly textured bismuth antimony flexible thermoelectric film, the steps are as follows: (1) Using high-purity elemental Bi, Sb and Zn as the initial raw materials, according to the chemical formula Bi 0.96 Sb 0.035 Zn 0.005 The raw materials are weighed and sealed in a quartz tube under a high vacuum environment. The quartz tube is then placed in a muffle furnace for melting reaction. The temperature is raised to 600°C at a heating rate of 5°C / min and kept at this temperature for 2h. The bismuth-antimony master alloy ingot is obtained by quenching with brine (saturated brine).
[0032] (2) Place the bismuth-antimony master alloy ingot in a melt spinning quenching device, and maintain the vacuum degree of the chamber at 5×10 -3 Pa; then, under the protection of argon atmosphere, the master alloy ingot is melted by induction heating, and then high-pressure argon is input into the quartz tube to form a high-speed jet of molten alloy, which is sprayed from the nozzle onto the rotating copper roller to complete the high-pressure spray spin quenching process, and finally a continuous film product is obtained. The specific process parameters are as follows: the spray pressure is 0.15 MPa, the copper roller linear speed is 10 m / s, the nozzle diameter is 0.5 mm, and the spray time is less than 10s.
[0033] In the temperature range of 50-300K, the conductivity, Seebeck coefficient and power factor of the thermoelectric film prepared in Example 2 were tested. The test results are shown in Table 2.
[0034] Table 2 Performance results of the thermoelectric film described in Example 2
[0035] It can be seen from Table 2 that the thermoelectric performance of the film prepared in Example 2 is further improved compared with that in Comparative Example 1, and its room temperature power factor reaches 43 μW·cm -1 ·K -2 According to the data in Table 2, after 100 bending cycles, the resistance of the film remained basically unchanged, showing excellent flexibility.
[0036] Example 3 A method for preparing a strongly textured bismuth antimony flexible thermoelectric film, the steps are as follows: (1) Using high-purity elemental Bi and Sb as the initial raw materials, according to the chemical formula Bi 0.99 Sb 0.01 The raw materials are weighed and sealed in a quartz tube under a high vacuum environment. The quartz tube is then placed in a muffle furnace for melting reaction. The temperature is raised to 600°C at a heating rate of 5°C / min and kept at this temperature for 2h. The bismuth-antimony master alloy ingot is obtained by quenching with brine (saturated brine).
[0037] (2) Place the bismuth-antimony master alloy ingot in a melt spinning quenching device, and maintain the vacuum degree of the chamber at 5×10 -3 Pa; then, under the protection of argon atmosphere, the master alloy ingot is melted by induction heating, and then high-pressure argon is input into the quartz tube to form a high-speed jet of molten alloy, which is sprayed from the nozzle onto the rotating copper roller to complete the high-pressure spray spin quenching process, and finally a continuous film product is obtained. The specific process parameters are as follows: the spray pressure is 0.15 MPa, the copper roller linear speed is 10 m / s, the nozzle diameter is 0.5 mm, and the spray time is less than 10s.
[0038] In the temperature range of 50-300K, the conductivity, Seebeck coefficient and power factor of the thermoelectric film prepared in Example 3 were tested. The test results are shown in Table 3.
[0039] Table 3 Performance results of the thermoelectric film described in Example 3
[0040] It can be seen from Table 3 that the room temperature power factor of the film prepared in Example 3 is 26 μW·cm -1 ·K -2 According to the data in Table 3, after 100 bending cycles, the resistance of the film remained basically unchanged, showing excellent flexibility.
[0041] Comparative Example 1 (1) Using high-purity elemental Bi and Sb as the initial raw materials, according to the chemical formula Bi 0.96 Sb 0.04The raw materials are weighed and sealed in a quartz tube under a high vacuum environment. The quartz tube is then placed in a muffle furnace for melting reaction. The temperature is raised to 600°C at a heating rate of 5°C / min and kept at this temperature for 2h. The bismuth-antimony master alloy ingot is obtained by quenching with brine (saturated brine).
[0042] (2) Place the bismuth-antimony master alloy ingot in a melt spinning quenching device, and maintain the vacuum degree of the chamber at 5×10 -3 Pa; then, under the protection of argon atmosphere, the master alloy ingot is melted by induction heating, and then high-pressure argon is input into the quartz tube to form a high-speed jet of molten alloy, which is sprayed from the nozzle onto the rotating copper roller to complete the high-pressure spray spin quenching process, and finally a continuous film product is obtained. The specific process parameters are as follows: the spray pressure is 0.03 MPa, the copper roller linear speed is 10 m / s, the nozzle diameter is 0.5 mm, and the spray time is less than 10s.
[0043] In the temperature range of 50~300K, the conductivity, Seebeck coefficient and power factor of the thermoelectric film prepared in Comparative Example 1 were tested. The test results are shown in Table 4.
[0044] Table 4 Performance results of the thermoelectric film described in Comparative Example 1
[0045] It can be seen from Table 4 that the room temperature power factor of the film prepared in Comparative Example 1 is 26 μW·cm -1 ·K -2 According to the data in Table 4, after 100 bending cycles, the resistance of the film remained basically unchanged, showing excellent flexibility, but (00 l ) plane orientation factor is only 0.05, indicating that (00 l ) The crystal planes have no obvious preferred orientation.
[0046] Figure 1 The following are the physical photos of the strongly textured bismuth antimony flexible thermoelectric film prepared in Example 1, the physical photos of the assembled planar device, and the SEM microstructure pictures, where a is the physical photo of the film, b is the physical photo of the assembled planar device, and c~d are the SEM microstructure pictures of the film. Figure 1 It can be seen that Example 1 prepared a continuous strip-shaped film with a thickness of 16 μm and a width of 5 mm, and the interior of the film was dense and uniform.
[0047] Figure 2The EDS spectrum results of the films prepared in Example 1 and Comparative Example 1 are compared, wherein a is the SEM image of the free surface of the film in Example 1, b is the distribution diagram of Bi and Sb elements on the free surface of the film in Example 1, c is the distribution diagram of Bi elements on the free surface of the film in Example 1, d is the distribution diagram of Sb elements on the free surface of the film in Example 1, e is the point scanning analysis result of the element content of the film in Example 1, and f is the point scanning analysis result of the element content of the film in Comparative Example 1. It can be seen from the figure that the constituent elements of the film in Example 1 are evenly distributed, forming a solid solution structure, and the element content is basically consistent with the nominal composition.
[0048] Figure 3 The XRD diagrams of the bismuth antimony films obtained in Examples 1 to 3 and Comparative Example 1 are shown. First, Figure 3 As can be seen in Figure a, according to the standard PDF card, Bi and Bi 1-x Sb x The strongest diffraction peak of the alloy appears on the (012) crystal plane. However, the prepared film shows significantly different characteristics: the (012) peak intensity is significantly weakened, while the strongest diffraction peak turns to (00 l ) crystal planes, including (003), (006) and (009) diffraction peaks, which indicates that the film has good (00 l ) orientation texture, it is calculated that (00 l ) plane orientation factor is 0.55. Further, according to Figure b, Zn doping reduces the Bi (00 l ) surface formation energy, the film (00 l ) orientation texture is significantly enhanced compared with Example 1, and the orientation factor increases to 0.78. Next, referring to Figure c, since the Sb element reduces the formation energy of the Bi (012) plane, the film sample shows a better (00 l ) preferred orientation, and the orientation factor reached 0.63. Finally, referring to Figure d, in Comparative Example 1, since the low-pressure spraying failed to produce an effective temperature gradient perpendicular to the contact surface of the copper roller when the alloy melt solidified, the film showed a (012) orientation feature, and did not form a (00 l ) oriented texture.
[0049] Figure 4 The conductivity, Seebeck coefficient and power factor of the bismuth antimony thin films obtained in Examples 1 to 3 and Comparative Example 1 are curves showing the changes with temperature, wherein a corresponds to the conductivity, b corresponds to the Seebeck coefficient, and c corresponds to the power factor. Figure 4 It can be seen that the thermoelectric film prepared by the present invention has good thermoelectric performance.
[0050] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A strongly textured bismuth antimony flexible thermoelectric film, characterized in that: Its chemical structure is Bi 1-x-y Sb x Zn y , x=0.005~0.05, y=0~0.02; the thickness of the thermoelectric film is 10~100μm, and the film is along (00 l ) The orientation factor of the crystal plane is 0.55~0.78, and the power factor is 26~43μW·cm at 300K -1 ·K -2 .
2. The strongly textured bismuth antimony flexible thermoelectric film according to claim 1, characterized in that: x=0.01~0.04, y=0~0.
005.
3. The method for preparing the strongly textured bismuth antimony flexible thermoelectric film according to any one of claims 1 to 2, characterized in that: The steps include: (1) According to the component ratio of the target chemical structure, Bi, Sb and Zn are mixed and melted at 500-800°C. After the reaction is completed, the reaction ingot is obtained by quenching with salt water; (2) placing the reaction ingot described in step (1) into a quartz tube with a nozzle, and placing it in a melt spinning quenching device; melting the reaction ingot by induction heating under a protective gas, and then inputting a protective gas with a pressure of 0.1-0.2 MPa to form a high-speed jet of the molten alloy, which is sprayed from the nozzle onto a copper roller with a rotating linear speed of 8-20 m / s, completing high-pressure spray spinning quenching, and finally obtaining a continuous film.
4. The method for preparing the strongly textured bismuth antimony flexible thermoelectric film according to claim 3, characterized in that: The purity of the Bi, Sb and Zn single substances in step (1) is greater than 99.9%.
5. The method for preparing the strongly textured bismuth antimony flexible thermoelectric film according to claim 3, characterized in that: The heating rate of the melting reaction in step (1) is 5-8°C / min; The melting reaction time of step (1) is 2 to 4 hours.
6. The method for preparing the strongly textured bismuth antimony flexible thermoelectric film according to claim 5, characterized in that: The temperature of the melting reaction in step (1) is 500-600°C.
7. The method for preparing the strongly textured bismuth antimony flexible thermoelectric film according to claim 3, characterized in that: The gas injection pressure in step (2) is 0.12-0.16 MPa.
8. The method for preparing the strongly textured bismuth antimony flexible thermoelectric film according to claim 7, characterized in that: The copper roller in step (2) rotates at a linear speed of 10-15 m / s.
9. The method for preparing the strongly textured bismuth antimony flexible thermoelectric film according to claim 3, characterized in that: The size of the nozzle in step (2) is 0.5-1 mm; The protective gas in step (2) is an inert gas or nitrogen.
10. Use of the strongly textured bismuth antimony flexible thermoelectric film according to any one of claims 1 to 2 in the preparation of low-temperature planar thermoelectric devices.